2016
DOI: 10.1155/2016/1058632
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Utility of Total IgE in Foods, Inhalant, and Multiple Allergies in Saudi Arabia

Abstract: Objective. To assess the diagnostic significance of total IgE in foods, inhalant, and multiple allergies. Methods. Retrospective review of the laboratory records of patients who presented with clinical suspicion of food or inhalant allergy between January 2013 and December 2014. Total IgE level was defined as positive for a value >195 kU/L; and diagnosis was confirmed by the detection of specific IgE (golden standard) for at least one food or inhalant allergen and at least two allergens in multiple allergies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Moreover, the estimated cost of asthma diagnosis and treatment is also on the rise [15]. Earlier research conducted in KSA and neighboring countries has drawn parallels to the reported clinical and immunological phenotypes [16,17]. Some of these studies reported a potential link between elevated blood eosinophilia and severe or uncontrolled asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the estimated cost of asthma diagnosis and treatment is also on the rise [15]. Earlier research conducted in KSA and neighboring countries has drawn parallels to the reported clinical and immunological phenotypes [16,17]. Some of these studies reported a potential link between elevated blood eosinophilia and severe or uncontrolled asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there has been considerable interest in the validity of total IgE level as diagnostic tool for allergy. However, the diagnostic value of total IgE levels seems to be limited, although many patients with allergic disorders have elevated levels of total IgE (121719272829303132). A Taiwanese study calculated that the cut-off value of total IgE for discriminating between an atopy and non-atopy group was 77.7 kU/L, with sensitivity and specificity of 82.3% and 87.1%, respectively (17).…”
Section: Discussionmentioning
confidence: 99%
“…A Taiwanese study calculated that the cut-off value of total IgE for discriminating between an atopy and non-atopy group was 77.7 kU/L, with sensitivity and specificity of 82.3% and 87.1%, respectively (17). A Saudi Arabian study also reported a total IgE specificity of 83.4% for the allergic group, but sensitivity was only 61.3% when the cut-off level was 195 kU/L (32). …”
Section: Discussionmentioning
confidence: 99%
“…Immunoglobulin E (IgE) is of central importance in the regulation of immune responses against parasitic infestations and most importantly, it is also recognized as a main mediator for immediate-type allergies or type I hypersensitivity reactions, such as allergic asthma, rhinitis, atopic diseases, anaphylaxis, etc. (Al-Mughales, 2016). It is a potent mast cell activator able to trigger mast cell degranulation and downstream responses with a minute amount (Actor, 2014).…”
Section: Inhibition Of Allergen-specific Igementioning
confidence: 99%